A comparative study of the ethical behavior of accounting students enrolled in the top five performing schools in Metro Manila - Cheng, Kevin Andrew Q. (Animo Repository, 2012)
In the past decade, the integrity and reliability of the accounting profession has been questioned due to the various corporate scandals. The increasing number of fraudulent financial reporting and various corporate collapses has distorted the trust of the private and public investors in the accounting profession. This study determined the current state of the ethical behavior of accounting students enrolled in the top five performing schools in Metro Manila. The study also determined if the ethical perception of students differs in the academic and business setting. The results of the study showed that students enrolled in the top five performing school are ethical in both the academic and business setting. Furthermore, there is no significant difference with the ethical behavior in the academic setting of respondents from different schools. It also showed that there is a significant difference with regards to the ethical behavior of the respondents in the business setting. The study also showed that age, church involvement, work experience, and business ethics integration are the factors that significantly influence students’ ethical behavior. Gender, on the other hand, has no significant influence to the ethical behavior of the students.